A goal set too high: factors associated with planning excess gestational weight gain in a prospective cohort study. (12th December 2022) - Lu, Cathy Huilin; Van Blyderveen, Sherry; Yu, Zhijie Michael; Vanstone, Meredith; Biringer, Anne; Sword, Wendy; Schmidt, Louis; McDonald, Sarah D.
Abstract: Objective: This study aimed to understand physical, knowledge, psychological, and lifestyle factors associated with planned excess gestational weight gain (GWG), a strong and potentially modifiable predictor of actual excess GWG, which contributes to maternal and child obesity along with other adverse maternal and fetal outcomes. Methods: This is a secondary analysis of data from a prospective cohort study where women completed a questionnaire in early pregnancy. Women were asked to report their planned GWG, which was then categorized as above, within, or below the Institute of Medicine (IOM) guidelines. Univariable and multivariable analyses were performed to identify variables associated with planned excess GWG. Results: Of 970 women included in the analysis, 300 reported a planned GWG above the IOM guidelines. Predictors of excess planned GWG included reporting healthcare provider recommendations to gain weight above the guidelines (adjusted odds ratio [aOR], 62.17; 95% confidence interval [CI], 13.75–281.03), overestimating first trimester weight gain recommendations (aOR, 1.83; 95% CI, 1.21–2.77), believing in risks to the baby with inadequate GWG (aOR 2.16; 95% CI, 1.29–3.60), inaccurate self-perceived prepregnancy body size (aOR, 1.88; 95% CI, 1.22–2.89), low or high emotional suppression (aOR, 1.78; 95% CI, 1.06–2.99; and aOR, 2.57; 95% CI, 1.21–5.45, respectively), physical inactivity (aOR, 1.10; 95% CI, 1.03–1.17), and overweight or obesity (aOR, 5.76; 95% CI, 3.70–8.98; and aOR, 11.46; 95% CI, 6.54–20.06, respectively). Protective factors against planned excess GWG included increased maternal age (aOR, 0.95; 95% CI, 0.92–0.99), and believing in risks to themselves with inadequate GWG (aOR 0.64; 95% CI, 0.42–0.97) or believing in risks to the baby with excess GWG (aOR, 0.49; 95% CI, 0.27–0.88). Conclusions: Women with overweight or obesity are at greater risk of prospectively planning excess GWG, and may especially benefit from healthcare provider counseling on appropriate GWG. Other modifiable factors for planned excess GWG included knowledge about risks of inappropriate weight gain and physical inactivity.